PERAN HUMAN CAPITAL DALAM MENINGKATKAN KINERJA PERUSAHAAN: SUATU TINJAUAN TEORITIS DAN EMPIRIS - Endri Endri (Jurnal Ilmu dan Budaya, 2010)
The present paper provides a review of the literature focusing relationship between human capital and performance essentially at firm level. The implement of review existing literature permitted to uncover three major neglected issues: 1). Defining and measuring the intelligence and human capital, 2). the analysis of human capital – firm performance relationship; and 3). Human resources management. A growing number of studies have attempted to show the link between human resources and firm performance.